Yielding and its adaptability of several promising bulk cocoa clones - Dedy Suhendi; Surip Mawardi; Hendro Winarno (Coffee and Cocoa Research Journal, 2005)
Yielding and its adaptability are considered to be an important criteria for clones recommendation. An experiment to evaluate yield and its adaptability of several promising bulk cocoa clones has been executed during 1996—2003 in three locations having different altitude and type of climate, consisted of Jatirono